DETERMINAN KINERJA USAHA KECIL DAN MENENGAH IKAN ASIN DI DESA TANJUNG BINGA KABUPATEN BELITUNG - Supriyadi, Supriyadi; Hidayatulloh, Amir (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to analyze the effect of the ability to compile finance report, motivation, and human resource competencies on the performance of SMEs. Respondents in the study used purposive sampling, with criteria for salty fish SMEs in Tanjung Binga Village, Belitung Regency, and at least the business had been operating for one year. The data analysis technique of this study used multiple linear regression analysis. This study found that the performance of SMEs influenced by the ability to compile the financial report, and human resource competencies. However, the performance of SMEs didn't influence by motivation. Keywords: Financial Report, Motivation, Human Resource Competencies, Performance, SMEs